A greater awareness of children with glucose‐6‐phosphate dehydrogenase deficiency is imperative in western countries. (15th February 2021) - Kristensen, Line; Lai, Amanda BK.; Ebbesen, Finn; Donneborg, Mette L.
Abstract: Aim: This national retrospective Danish study described the characteristics of children diagnosed with glucose‐6‐phosphate dehydrogenase (G6PD) deficiency, an inherited X‐linked recessive disorder that often affects children of Middle Eastern descent. Methods: We studied children born between 1 January 2000 and 31 December 2017 and diagnosed with G6PD deficiency. They were identified from the Danish National Hospital Discharge Register and the Danish Database of Extreme Neonatal Hyperbilirubinaemia. Results: There were 113 children diagnosed with G6PD deficiency, 67% were of Middle Eastern descent and they were frequently diagnosed before the onset of symptoms, based on known heredity. Of the 67 infants born in Denmark, 10% had extreme neonatal hyperbilirubinaemia and one developed kernicterus spectrum disorder, as did one child born in the Middle East. Most (61%) of the 33 children with jaundice received phototherapy, 12% had exchange transfusions and 18% received whole blood transfusions. After the neonatal period, 23% of the cohort had blood transfusions and 4% needed intensive care for acute haemolytic anaemia. The incidence of G6PD deficiency appeared to be severely underestimated. Conclusion: Many families from countries where G6PD deficiency is endemic move to Denmark and other Western countries. Greater awareness is essential to avoid chronic and potentially lethal, consequences.